2011
DOI: 10.1007/s12015-011-9274-2
|View full text |Cite
|
Sign up to set email alerts
|

Human Serum is as Efficient as Fetal Bovine Serum in Supporting Proliferation and Differentiation of Human Multipotent Stromal (Mesenchymal) Stem Cells In Vitro and In Vivo

Abstract: Human serum can support proliferation and differentiation of hMSC in vitro and can maintain their bone forming capacity in vivo. The use of human serum in cell cultures of hMSC intended for cell-based therapy is preferable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
62
0
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(68 citation statements)
references
References 31 publications
4
62
0
2
Order By: Relevance
“…Human Serum (HS): Overall, HS allowed for the isolation and expansion of BMSC, ASC, DPSC maintaining proper cell biological properties both in vitro and in vivo (48,(80)(81)(82)(83)(84)(85). Both, 10% HS in DMEM/F-12 or 5%-10% HS in αMEM provided, to ASC and BMMSC, proliferation rates and multipotency as higher as 10% FBS (24,48,51,(86)(87)(88).…”
Section: Resultsmentioning
confidence: 99%
“…Human Serum (HS): Overall, HS allowed for the isolation and expansion of BMSC, ASC, DPSC maintaining proper cell biological properties both in vitro and in vivo (48,(80)(81)(82)(83)(84)(85). Both, 10% HS in DMEM/F-12 or 5%-10% HS in αMEM provided, to ASC and BMMSC, proliferation rates and multipotency as higher as 10% FBS (24,48,51,(86)(87)(88).…”
Section: Resultsmentioning
confidence: 99%
“…Scale bar =200 µm. (Aldahmash et al, 2011;Wang et al, 2012). Previously we have observed that human eyelid adiposederived stem cells could aggregate during high-density culture in the presence of HS (Song et al, 2012).…”
Section: Protein Expression Of Jam2 Moleculementioning
confidence: 96%
“…Among the blood-derived components, human AB serum (AB HS) can be considered a promising FBS alternative due to its availability and possibility of autologous usage [6]. Various studies have reported on the successful use of this supplement for different types of cells, including MSCs [4,[6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Various studies have reported on the successful use of this supplement for different types of cells, including MSCs [4,[6][7][8][9][10][11]. However, none of these studies have addressed different sources to produce AB HS or con-…”
Section: Introductionmentioning
confidence: 99%